ChemInform Abstract: Hydrothermal Liquefaction for Algal Biorefinery: A Critical Review. Issue 29 (July 2015) - Tian, Chunyan; Li, Baoming; Liu, Zhidan; Zhang, Yuanhui; Lu, Haifeng
Abstract Review: 166 refs.